A study to assess patient satisfaction in out patient department of a tertiary care hospital in north India - Jain, Aanchal; Mishra, Neha; Pandey, C. M. (International Journal Of Community Medicine And Public Health, 2017)
Background: OPD is very crucial department of any hospital services as huge number of patient’s visits the OPD. Yet, the published information about patients' profile and utilization of OPD services in both developing and developed countries is scarce. The objective of our study was to study the socio-demographic profile, patient’s satisfaction towards hospital services and pattern of referral of the outdoor patients visiting Sanjay Gandhi Post Graduate Institute of Medical Sciences, Lucknow, India. Methods: It is a cross-sectional survey of patients visiting OPD in a tertiary care hospital in Lucknow. Data was collected by a structured questionnaire designed for the purpose. Results: A total of 200 patients were included in the study with average age of 40 years. The majority of patients (40%) were graduate & above. No patient was found illiterate in our study. 74.5% of the patients are currently married. 25% of the total were employed in some service, 9% were doing business. 27.5% were unemployed or students. The main presentation was Cardiac disease (20%) and Gastric problems (18.5%), followed by kidney problems (13%). 69% patients were referred to a tertiary care hospital by a doctor as a first referral. Outcome of first treatment & distance of patient’s usual place of residence from a tertiary care hospital was found to be significantly associated with referral pattern. Patient’s satisfaction towards OPD services were found to be associated with Caste, occupation, outcome of first treatment & distance of patients usual place of residence from hospital. All of the patients are highly satisfied with doctors (97%) while they were least satisfied by canteen (31.6%), transport (31.1%) & pharmacy services (25.6%). Conclusions:Overall the study showed a good level of satisfaction of patients with services obtained from this tertiary care centre. Appropriate and on-going data collection and analysis could help in optimizing utilization of outpatient services to achieve better outcomes.